Counterlife : Slavery after Resistance and Social Death - Freeburg, Christopher (Book collections on Project MUSE., 2021)
"Counterlife demonstrates that scholarship on slavery in the Americas has its imaginative roots in the emergence of sociology/social theory in the 1950s as well as aesthetic movements (e.g., naturalism and modernism) that flourished in the early twentieth century. Debates between social scientists, artists, and politicians about mass culture, modern urban space, and socialization amplify slavery studies' preoccupation with political insurgency and resistance. This book analyzes the kinds of descriptions of social space, power, and personality type that became pivotal in the early sociology and psychology of slavery studies"--